Evaluation of the use of PEEK material in post-core and crown restorations using finite element analysis - Tekin, Samet; Adiguzel, Ozkan; Cangul, Suzan; Atas, Osman; Erpacal, Begum (Mosher & Linder, Inc, 2020)
Purpose: To compare the stresses generated after the use of low elastic modulus polyetheretherketone (PEEK) as dental post and crown material with glass fiber post and metal supported ceramic crowns using finite element analysis. Methods: First an image of a maxillary central incisor taken on micro-computed tomography (microCT) was uploaded to a computer program. Modeling was made of all the materials in the computer environment and 3-dimensional (3D) virtual models were obtained. Using two different post materials (glass fiber and PEEK post) and two different crown materials (metal supported ceramic and PEEK crown), the modeling of the maxillary central tooth was completed and a total of four groups were obtained. Finally, 135 degrees and 100 N forces were applied from the midpoint of the palatal surface. Results: The FEA analysis showed the use of PEEK as post material decreased the stress values in the post, post cement and composite core models and did not have any significant change in the dentin and crown cement models. The use of composite veneer with PEEK substructure as crown material reduced stress values in dentin, the post and composite core and increased stress values in both the post cement and the crown cement.
Keywords: Glass-Fiber; Fracture-Resistance; Stress-Distribution; Biomechanical Behavior; Composite Resin; Bond Strength; Teeth; Posts; Root; Tooth